Which green nudge helps to save energy? Experimental evidence - Christoph Bühren; Maria Daskalakis (Philipps-University Marburg, School of Business and Economics, 2020)
Which behavioral interventions are more appropriate to induce energy saving: energy saving goals with or without monetary incentives, environmentally related information, social comparison, or a competition to save energy? We try to answer this question in a comprehensive study. First, we designed energy bills with different behavioral interventions. Second, we evaluated their appropriateness in an empirical survey with 457 participants. Third, we tested behavioral consequences in a “real effort” lab experiment with 550 subjects in 11 treatments and one baseline. Finally, we tested two interventions in a small field experiment with 36 test-households. Our results indicate that monetary incentives to save energy foster the intention to invest effort in energy saving but may backfire if real effort is required. Instead, self-set goals – without monetary incentives – and providing social comparison induced substantial effort in our lab experiment. Extending the social comparison to a competition – without monetary incentives – provided the best results. In our field experiment, however, we find no support that goals and social comparison change every-day behavior in energy consumption. Our study concludes with implications for practical policy design and possible future research.
Keywords: D03; D12; C91; 330; Energy-saving; Goals; Social Comparison; Competition; Real effort experiment